2017
DOI: 10.1111/1440-1681.12803
|View full text |Cite
|
Sign up to set email alerts
|

The use of antioxidant agents for chemotherapy‐induced peripheral neuropathy treatment in animal models

Abstract: SummaryAntineoplastic drugs such as cisplatin, oxaliplatin, paclitaxel and vincristin are widely used in the treatment of several solid and blood tumours. However, the severity of peripheral neuropathy caused by these agents can affect the patient's quality of life.The major symptoms of chemotherapy-induced peripheral neuropathy (CIPN) involve: sensory loss, paresthesia, dysesthaesia, numbness, tingling, temperature sensitivity, allodynia and hyperalgesia, in a "stocking and glove" distribution. Why many diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
0
11
0
2
Order By: Relevance
“…[6][7][8] Specifically, ROS scavengers such as N-tert-butyl-α-phenylnitrone, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl and vitamin E were shown to reverse mechanical allodynia. [9][10][11] Though ROS is known to play a major role in establishing and maintaining NP, there is a shortage of effective clinical treatments that primarily target ROS system. Collectively, these studies suggest that ROS play an important role in central sensitization mechanism for mechanical allodynia and it is worth studying the effect of ROS scavengers in neuropathic pain treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Specifically, ROS scavengers such as N-tert-butyl-α-phenylnitrone, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl and vitamin E were shown to reverse mechanical allodynia. [9][10][11] Though ROS is known to play a major role in establishing and maintaining NP, there is a shortage of effective clinical treatments that primarily target ROS system. Collectively, these studies suggest that ROS play an important role in central sensitization mechanism for mechanical allodynia and it is worth studying the effect of ROS scavengers in neuropathic pain treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Поскольку описанный механизм является ключевым в физиопатологии химиоиндуцированной периферической нейропатии, считается, что антиоксидантная терапия является эффективной альтернативой для предотвращения развития ХИПН [42]. Рецепторы, активируемые пролифераторами пероксисом (РАПП), являются важными членами семейства ядерных рецепторов, которые вызывают активацию нескольких генов, действуя в качестве лиганд-активированного фактора транскрипции [43].…”
Section: оригинальные статьиunclassified
“…As evidenced by many oxidative stress models, tea and polyphenols can prevent or attenuate the decrease of antioxidant enzyme activity. Supplementation of green tea polyphenols to drinking water can significantly inhibit the decrease of catalase and glutathione reductase activity in epidermis of hairless mice induced by UVB [9]. In addition, oral test in mice infected with Mycobacterium tuberculosis showed that green tea extract could also prevent the decrease of superoxide dismutase activity [10].…”
Section: Animal Modelsmentioning
confidence: 99%
“…However and importantly, antioxidant agents have protective effects on free radical damage. The therapeutic effect of antioxidants on peripheral neuropathy has been detected by many studies with established animal models [9]. Additionally, research team led by Gong [12] and Vashistha [13] studied the effect of matrine and ferulic acid on vincristine-induced neuropathic pain in animal models, respectively.…”
Section: Animal Modelsmentioning
confidence: 99%